Estilo de vida y su influencia en la diabetes mellitus en paciente que asisten en el Hospital General IESS Babahoyo en el periodo noviembre 2023 - abril 2024. - García Macias, Nathaly Margoth (2024)
Modern lifestyles have led to sedentary behaviors, less participation in active movement and physical activities during leisure time, unhealthy diets, and increased exposure to stress. It is important to examine the interaction of several lifestyle risk factors rather than focusing on just one. The purpose of this study was to determine the lifestyles that influence diabetes mellitus in patients attending the IESS Babahoyo general hospital in the period November 2023-April 2024. The methodology applied was quantitative, descriptive, and experimental, the sample consists of 96 patients treated at the IESS Babahoyo General Hospital during the period November 2023 - April 2024.